Fabrication of Ordered Macroporous TiO2/SiO2 Composite from Preformed Water-Soluble TiO2 Nanocrystals and Silicon Alkoxide - Liu, Guodong; Wang, Tongwen; Liu, Ling; Wang, Mengxi; Dong, Yi (Asian Journal of Chemistry, 2011)
An aqueous suspension containing preformed water-soluble TiO2 nanocrystals and tetraethylorthosilicate was used to fill interstices of closed-packed poly(methyl methacrylate) spheres by a centrifugation sedimentation method and finally create three-dimensional ordered macroporous TiO2/SiO2 composite. SEM images show that the macroporous composite obtained exhibits a long-range hexagonal ordered array of spherical macropores with a pore size of about 214 ± 5 nm. XRD and HRTEM results reveal that the TiO2 particles with a grain size of about 9 nm and a crystalline anatase phase structure are embedded in the macroporous silica walls.